James Noble Mackenzie's Ministry in South Korea : a Missiological Exploration from a Minjung Perspective - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.